Generation of additive colors with near unity amplitude using a multilayer tandem Fabry-Perot cavity - Kosger, Ali Cahit; Ghobadi, Amir; Rashed, Alireza Rahimi; Caglayan, Humeyra; Ozbay, Ekmel (Optics letters, 2021)
In this paper, the generation of additive red-green-blue (RGB) colors in reflectance mode with near unity amplitude is demonstrated. For this purpose, a multilayer structure made of metal-insulator-metal-semiconductor-insulator stacks is designed to achieve >0.9 reflection peaks with full-width-at-half-maximum values <0.3λpeak. The proposed design also shows near zero reflection in off-resonance spectral ranges, and this, in turn, leads to high color purity. The optimized designs are fabricated, and simulation and theoretical results are verified with characterization findings. This work demonstrates the potential of multilayer tandem cavity designs in the realization of lithography-free large-scale compatible functional optical coatings.In this paper, the generation of additive red-green-blue (RGB) colors in reflectance mode with near unity amplitude is demonstrated. For this purpose, a multilayer structure made of metal-insulator-metal-semiconductor-insulator stacks is designed to achieve >0.9 reflection peaks with full-width-at-half-maximum values <0.3λpeak. The proposed design also shows near zero reflection in off-resonance spectral ranges, and this, in turn, leads to high color purity. The optimized designs are fabricated, and simulation and theoretical results are verified with characterization findings. This work demonstrates the potential of multilayer tandem cavity designs in the realization of lithography-free large-scale compatible functional optical coatings.